2019
DOI: 10.1002/chem.201900790
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Hydrogen‐Adsorption Free Energy of Ru‐Based Catalysts towards High‐Efficiency Hydrogen Evolution Reaction at all pH

Abstract: The utilization of noble‐metal catalysts for the hydrogen evolution reaction (HER) provides an efficient strategy for hydrogen acquisition. However, exploring catalysts with suitable hydrogen binding strength for the HER process is always of great importance, but extremely challenging. In this work, sulfur and phosphor as electron‐withdrawing elements were incorporated into carbon nanotube (CNT)‐supported Ru catalysts, which were prepared through a facile solution reduction reaction and post thermo treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 40 publications
1
14
0
2
Order By: Relevance
“…Section 3 provides several representative descriptors developed by DFT calculations, including the binding energy, formation energy, [24][25][26] d-band center, [27][28][29] scaling relations, [30][31][32][33] e g orbital occupation, [34][35][36] and free energy of adsorption. [37][38][39] Meanwhile, at Section 4, we will describe the practical tools derived from DFT calculations, which are useful for further investigation of the electrocatalytic activity. Section 5 gives a brief introduction of the catalytic mechanisms of specific electrocatalytic reactions, including HER, ORR, CO 2 RR, and NRR.…”
mentioning
confidence: 99%
“…Section 3 provides several representative descriptors developed by DFT calculations, including the binding energy, formation energy, [24][25][26] d-band center, [27][28][29] scaling relations, [30][31][32][33] e g orbital occupation, [34][35][36] and free energy of adsorption. [37][38][39] Meanwhile, at Section 4, we will describe the practical tools derived from DFT calculations, which are useful for further investigation of the electrocatalytic activity. Section 5 gives a brief introduction of the catalytic mechanisms of specific electrocatalytic reactions, including HER, ORR, CO 2 RR, and NRR.…”
mentioning
confidence: 99%
“…They all were close to 0 eV, which indicated that the heterojunction did not have the adsorption effect on hydrogen aer the generation of hydrogen, and the generated hydrogen could actively diffuse and failed to form hydrogen molecules clustered around the active site. 67…”
Section: Resultsmentioning
confidence: 99%
“…The C-C, C-C and C-N bonds are derived from the carbon skeleton of polypyrrole carbon nanotubes, and the existence of C-N bond proves that there is N atom doping in the carbon skeleton. 29,30 The weak peak of C]O bond is caused by the absorption of oxygen or carbon dioxide and the oxidation of a small amount of surface metal ruthenium particles. 31 Three typical types of nitrogen elements can be observed in Fig.…”
Section: Resultsmentioning
confidence: 99%